2018
DOI: 10.1111/jnc.14552
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral microdialysis of adenosine and adenosine monophosphate – a systematic review and meta‐regression analysis of baseline concentrations

Abstract: Microdialysis is a method to study the extracellular space in vivo, based on the principle of diffusion. It can be used to measure various small molecules including the neuroregulator adenosine. Baseline levels of the compounds measured with microdialysis vary over studies. We systematically reviewed the literature to investigate the full range of reported baseline concentrations of adenosine and adenosine monophosphate in microdialysates. We performed a meta‐regression analysis to study the influence of flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 117 publications
1
25
0
Order By: Relevance
“…The median adenosine concentration over the remaining 601 samples was 0.36 nM and the values found ranged from a minimum of 0.004 nM to a maximum of 27 nM. This is within the range of reported concentrations in our preceding systematic review [28]. Preliminary analyses of time curves, depicted in Figure 1, indicated high variability in some rats.…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…The median adenosine concentration over the remaining 601 samples was 0.36 nM and the values found ranged from a minimum of 0.004 nM to a maximum of 27 nM. This is within the range of reported concentrations in our preceding systematic review [28]. Preliminary analyses of time curves, depicted in Figure 1, indicated high variability in some rats.…”
Section: Resultssupporting
confidence: 75%
“…Within our previously described sample of 132 adenosine microdialysis studies [28], we identified nine papers measuring microdialysate adenosine levels during sleep deprivation. Eight of these papers (described in Table 1) reported dialysate adenosine concentrations during sleep deprivation and prior baseline, one [36] directly compared concentrations between groups only and could not be included in the meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations